Pengetahuan dan operator konsep dalam pembelajaran Matematik tahun 2 - Anna, Parir. (Universiti Malaysia Sarawak (UNIMAS), 2003)
This research aims to identify the knowledge and concept operator used in learning Mathematics for year two primary school students. This research used verbal protocol analysis to identify the knowledge slate, C{)nceptua/ operator and cognitive processes involved during learning Mathematics. Subjects were required to solve the activity given and thinking-aloud data was collected. From this study the knowledge states identified were Mathematical data, Mathematical skills, Mathematical operation and problem solving technique. The conceptual operators identified include data examination, data exploration, data explanation, meta-reasoning and summarization. Overall, by using the knowledge states and operators, the learning model for year two mathematics students was developed. The findings ofthis research could assist teachers to improve on their teaching methods and teaching design in Mathematics.